Design and control of a multifingered anthropomorphic robotic hand / Ahmed Jaffar ... [et al.] - Ahmed, Jaffar; Bahari, Mohd Bahari; Cheng, Yee Low; Jaafar, Roseleena (IJENS Publishers, 2011)
This work describes a multifingered anthropomorphic robotic hand with fourteen degrees of freedom which is able to mimic the functional motions of a biological hand especially in handling complex objects. The actuation mechanisms consisting of micro servo-motors, pulleys and belts are connected to the finger joints and thereby bending and extending the fingers. Two kinds of sensors, i.e. force sensor and light dependent resistor, are integrated into the system. The robotic hand can be controlled via a graphical user interface embedded with control codes or a joy stick integrated with a control board. Furthermore, the robotic hand is able to operate autonomously with the aid of the sensory elements and the embedded control software. Workability tests showed the capability of the system to move every finger individually and to perform grasping tasks on objects with varying sizes and geometries such as a tennis ball and a screw driver.